Neutron dark-field imaging applied to porosity and deformation-induced phase transitions in additively manufactured steels. (October 2020) - Bacak, M.; Valsecchi, J.; Čapek, J.; Polatidis, E.; Kaestner, A.; Arabi-Hashemi, A.; Kruk, I.; Leinenbach, C.; Long, A.M.; Tremsin, A.; Vogel, S.C.; Watkins, E.B.; et al.
Abstract: Neutron dark-field imaging (DFI) was used to investigate the microstructure of additive manufactured steels. Several DFI methods were combined to assess the microstructure over more than two orders of magnitude in size. Different degrees of porosity and other building features were found depending on the parameters of the selective laser melting additive manufacturing process. A sample built with processing parameters yielding the lowest porosity was deformed which induced a phase transformation of the austenitic phase (fcc) into the martensitic phase (bcc). In the deformed sample an increased dark-field contrast was observed which can only be explained by accounting for the fcc-bcc phase distribution and the magnetic properties of the martensitic phase. We demonstrate that neutron dark-field imaging is well suited to not only detect build flaws like cracks but quantitatively characterize the microstructure in additive manufactured steels. Graphical abstract: Image 1 Highlights: Porosity study in additively manufactured steels via neutron dark field imaging. Three set-ups cover nearly three orders of magnitude in microstructure size Successful merging of data from different experimental set-ups Deformation induced phase transformation of the steel causes strong contrast. Dark field imaging allows to determine the phase ratio in the steel.